Diagnosis of Bovine Genital Campylobacteriosis in South America - Silveira, Caroline da Silva; Fraga, Martin; Giannitti, Federico; Macías-Rioseco, Melissa; Riet-Correa, Franklin (Frontiers in Veterinary Science, 2018)
Bovine genital campylobacteriosis (BGC) is a venereal infectious disease that affects reproduction. It is caused by the Gram-negative bacillus Campylobacter fetus subspecies venerealis (Cfv), which may include the biotype intermedius. The bull is a lifelong asymptomatic carrier and transmitter of the disease. In females Cfv may cause infertility and sporadic abortion. The objective of this study is to review and discuss methods for the diagnosis of BGC, its prevalence and economic impact in South America. BGC is a worldwide distributed disease and can cause a pregnancy rate decrease of 15–25%. The farm prevalence of BGC in different regions of South American countries shows a variation between 2.3 and 100%. Discrepancies may depend on the differences on sanitary, management, and reproductive practices between farms and regions, but also on the interpretation of different diagnostic tests. Currently known laboratory tests include bacterial culture, direct immunofluorescence, immunoenzymatic assays, vaginal mucus agglutination test, PCR-based methods, histology and immunohistochemistry, which are applied and interpreted in diagnostic laboratories at different scales. Epidemiologic data of BGC in South America should be interpreted with caution. High prevalence has been reported in some studies, although the low specificity of the diagnostic tests used could lead to an overestimation of the results.